Irisin immunohistochemistry in gastrointestinal system cancers - Aydin, S.; Kuloglu, T.; Ozercan, M. R.; Albayrak, S.; Aydin, S.; Bakal, U.; Balgetir, F. (Taylor & Francis Ltd, 2016)
Cancer is the leading cause of morbidity and mortality worldwide. Some studies have shown that high heat kills cancer cells. Irisin is a protein involved in heat production by converting white into brown adipose tissue, but there is no information about how its expression changes in cancerous tissues. We used irisin antibody immunohistochemistry to investigate changes in irisin expression in gastrointestinal cancers compared to normal tissues. Irisin was found in human brain neuroglial cells, esophageal epithelial cells, esophageal epidermoid carcinoma, esophageal adenocarcinoma and neuroendocrine esophageal carcinoma, gastric glands, gastric adenosquamous carcinoma, gastric neuroendocrine carcinoma, gastric signet ring cell carcinoma, neutrophils in vascular tissues, intestinal glands of colon, colon adenocarcinoma, mucinous colon adenocarcinoma, hepatocytes, hepatocellular carcinoma, islets of Langerhans, exocrine pancreas, acinar cells and interlobular and interlobular ducts of normal pancreas, pancreatic ductal adenocarcinoma, and intra- and interlobular ducts of cancerous pancreatic tissue. Histoscores (area x intensity) indicated that irisin was increased significantly in gastrointestinal cancer tissues, except liver cancers. Our findings suggest that the relation of irisin to cancer warrants further investigation.
Keywords: cancer; gastrointestinal system; immunohistochemistry; irisin